Designed filamentous cell penetrating peptides: probing supramolecular structure-dependent membrane activity and transfection efficiency1. Issue 59 (28th July 2015) - Xu, Dawei; Dustin, Derek; Jiang, Linhai; Samways, Damien S. K.; Dong, He
<x xml:space="preserve">Abstract</x> In this work, we will demonstrate the supramolecular assembly of single-chain cationic peptides into stable macromolecular filamentous nanostructures and investigate their supramolecular structure-dependent membrane activity for the development of highly efficient therapeutic carriers.